New Representations of Spherical Indicatricies of Bertrand Curves in Minkowski 3-Space. (28th January 2015) - Aydemir, İsmail; Yerlikaya, Fırat
Abstract : We obtained a new representation for timelike Bertrand curves and their Bertrand mate in 3-dimensional Minkowski space. By using this representation, we expressed new representations of spherical indicatricies of Bertrand curves and computed their curvatures and torsions. Furthermore in case the indicatricies of a Bertrand curve are slant helices, we investigated some new characteristic features of these curves.